2014
DOI: 10.1103/physreve.90.050102
|View full text |Cite
|
Sign up to set email alerts
|

Machta-Zwanzig regime of anomalous diffusion in infinite-horizon billiards

Abstract: We study diffusion on a periodic billiard table with an infinite horizon in the limit of narrow corridors. An effective trapping mechanism emerges according to which the process can be modeled by a Lévy walk combining exponentially distributed trapping times with free propagation along paths whose precise probabilities we compute. This description yields an approximation of the mean squared displacement of infinite-horizon billiards in terms of two transport coefficients, which generalizes to this anomalous re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…Here η is a free parameter which cannot be determined uniquely by the aforementioned steps alone. We found that taking η = 1 produces good results for P (x, N ) and alternatively for P d (r, t), see Figs 4,5,9, Each plot consists out of approximately 10 6 points. The Lorentz gas displays strong similarity between repeated draws and the simulation data, meaning that the renewal condition is indeed fulfilled.…”
Section: Discussion and Summarymentioning
confidence: 85%
See 2 more Smart Citations
“…Here η is a free parameter which cannot be determined uniquely by the aforementioned steps alone. We found that taking η = 1 produces good results for P (x, N ) and alternatively for P d (r, t), see Figs 4,5,9, Each plot consists out of approximately 10 6 points. The Lorentz gas displays strong similarity between repeated draws and the simulation data, meaning that the renewal condition is indeed fulfilled.…”
Section: Discussion and Summarymentioning
confidence: 85%
“…one neglects correlations between consecutive collisions. It was shown that for the cross-like configuration of the Lorentz gas and in the limit of large scattering centers, this condition is nullified as an effective trapping mechanism emerges [4]. In contrast, when the scattering centers are not too large, the Lévy walk with the obtained cumulative distribution function (CDF) of the waiting times works perfectly, as demonstrated below.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The latter process was observed when tracking trajectories of a Hamiltonian particle moving over an egg-grate potential; see Klafter and Zumofen (1994). Adapted from Klafter, Shlesinger, and Zumofen, 1996. type of two-dimensional Lévy walks with the exponent γ ¼ 2 is relevant for the description of the diffusion in Sinai billiards with infinite horizon (Bouchaud and Georges, 1990), as shown recently by Cristadoro et al (2014).…”
Section: Discussionmentioning
confidence: 95%
“…The Lorentz gas (LG) is a classical model of transport [1,2], in which a pointlike particle moves at a constant speed, while undergoing elastic collisions with fixed scatterers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. When the free paths in this model are unbounded, it is termed the infinite-horizon LG (see Ref.…”
mentioning
confidence: 99%